Effect of Na+ and Ca2+ on the Thermal Degradation of Carboxymethylcellulose in Air. Issue 4 (May 2017) - Tan, Liwen; Shi, Ran; Ji, Quan; Wang, Bingbing; Quan, Fengyu; Xia, Yanzhi
Carboxymethylcellulose (CMC), including the acid form (CMC-H) and salt forms (CMC-Na, CMC-Ca), were prepared for the survey of thermal degradation and the CMC-H was obtained by acidifying CMC-Na with HCl. An online-coupled thermogravimetric (TG)-FTIR evolved gas analysis instrument was used to identify and monitor the evolution of gaseous products during the thermal degradation of CMC in air. The thermal degradation characteristics of CMC-H and salt forms CMC-Na, CMC-Ca of carboxymethylcellulose were compared to determine the effect of Na + and Ca 2+ counter-ions on CMC thermal degradation in air. From the TG and DTG curves, thermal degradation of the samples occurred in three stages. During the second stage (200–410 °C) major degradation occurred, accompanied by a large weight loss. The 3D FTIR absorbance spectra and Gram-Schmidt curves of the evolved gases were obtained. In compounds CMC-Na and CMC-Ca, the initial degradation temperature is higher, the rate of CMC degradation increases, and the weight loss in the temperature range 200–410 °C decreases. These samples also catalyse the stable intermediate products in the temperature range 410–600 °C.